Mediation role of economic freedom in the nexus between financial integration and inclusive growth in Africa - Khadijah Iddrisu; Simplice A. Asongu; Eric Kofi. Boadi (Humanities & Social Sciences Communications)
Abstract The financial integration literature has mostly focused on traditional growth measures, which is a narrow form of growth. To enhance the body of knowledge on financial integration, this study addresses a gap in the existing literature by adopting a broader perspective on growth, specifically focusing on inclusive growth. Also, it has largely neglected one of the mechanisms through which financial integration enhances growth. Consequently, this study contributes to the existing knowledge by analysing how economic freedom mediates the relationship between financial integration and inclusive growth in a panel of 48 African countries from 2000 to 2021. The empirical results are based on the instrumental variable generalised method of moments (IV-GMM). The findings show that financial integration promotes inclusive growth in Africa. In addition, the results revealed a partial mediation effect of economic freedom in the financial integration-inclusive growth nexus. The study recommends that policymakers should simplify regulations and cut bureaucratic hurdles for financial institutions and businesses. Strengthening legal frameworks to protect property rights and enforce contracts is essential for economic freedom. This enhances investor confidence, aids financial integration, and promotes inclusive growth.